1979
DOI: 10.1104/pp.63.3.518
|View full text |Cite
|
Sign up to set email alerts
|

Proline Accumulation in Water-stressed Barley Leaves in Relation to Translocation and the Nitrogen Budget

Abstract: Mobilization of N from leaves of barley (Hordeum vulgare L.) during water stress, and the role of proline as a mobilized species, were examined in plants at the three-leaf stage. The plants responded to water stress by withdrawing about 25% of the total reduced N from the leaf blades via phloem translocation. Most of this N loss was during the first 2 days while translocation of 'C-photosynthate out of the stressed blade still remained active. Free proline accumulation in the blade was initially slow, and beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
25
0
1

Year Published

1979
1979
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 16 publications
3
25
0
1
Order By: Relevance
“…whole blade. The latter values may be compared directly with the value of 260 I&g N exported/ day-leaf, derived from N balance data for barley leaves stressed for 1 day (16). Glutamine and glutamate together accounted for about 30%o of this rate, whereas proline accounted for about 3%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…whole blade. The latter values may be compared directly with the value of 260 I&g N exported/ day-leaf, derived from N balance data for barley leaves stressed for 1 day (16). Glutamine and glutamate together accounted for about 30%o of this rate, whereas proline accounted for about 3%.…”
mentioning
confidence: 99%
“…It has been reported that leaves absorb gaseous NH3 and 15NH3 (4,8), incorporate 15NH3 into amino acids and protein, and export some of the assimilated 15N to roots (12). The pathway for assimilation of NH3, which is clearly active in turgid leaves (10,12), is most probably also active in water-stressed leaves because the NH4, pools of leaves do not increase markedly during stress and little NH3 is volatilized from stressed leaves, despite extensive protein catabolism (1,16 under a bank of fluorescent tubes (15). After 30 min, the fed leaf was rapidl, excised and divided into blade and sheath portions.…”
mentioning
confidence: 99%
“…3), there are few previous reports on the nitrogenous phloem constituents in these crops ( 18). The N-compounds moving in the phloem of cereals may originate from either or both of the following sources: (a) recent N assimilation (18,23 and refs. cited therein), and (b) hydrolysis of leaf proteins, which occurs during senescence (1) and episodes of water stress (23).…”
mentioning
confidence: 99%
“…The N-compounds moving in the phloem of cereals may originate from either or both of the following sources: (a) recent N assimilation (18,23 and refs. cited therein), and (b) hydrolysis of leaf proteins, which occurs during senescence (1) and episodes of water stress (23). Although it is clear that the relative importance of sources (a) and (b) changes both with developmental stage and with environmental conditions, little is known about the chemical forms of N which these sources make available for phloem transport.…”
mentioning
confidence: 99%
See 1 more Smart Citation